Integrated versus non-integrated peripheral intravenous catheters: a cross-sectional survey of nurse experiences. (26th January 2023) - Paterson, Rebecca S; Larsen, Emily N; Cooke, Marie; Rickard, Claire M; Walker, Rachel M; Marsh, Nicole
Abstract : Background: Integrated peripheral intravenous catheters (PIVCs) demonstrate clinical efficacy, however, device complexity and design differences may be a potential barrier to implementation. Aims: To assess nurse acceptability of integrated PIVC systems. Methods: A cross-sectional survey was nested within a multicentre randomised controlled trial. One hundred nurses caring for patients with integrated and non-integrated PIVCs completed a 17-item survey about key differences between devices (eg function and appearance, perceived patient comfort and skin injuries). Findings: Most nurses reported the integrated PIVC wings prevented device movement (80%), achieved patient comfort in areas of flexion (78%), and no patients developed skin injuries (100%). Nurses rated the ease of accessing and overall confidence using the integrated PIVC as significantly higher than the non-integrated design ( P <0.001).Conclusion: The integrated PIVC received positive feedback from nurses and had few barriers to implementation.